PERLINDUNGAN HUKUM TERHADAP PEMEGANG HAK MILIK ATAS TANAH YANG BELUM BERSERTIFIKAT DENGAN ITIKAD BAIK MENURUT PERATURAN PEMERINTAH NOMOR 24 TAHUN 1997 TENTANG PENDAFTARAN TANAH - Muskur, La Ode Muhammad; Taibu, Rachmat; Rais, La Ode Muhammad Rijal (Fakultas Hukum Universitas Dayanu Ikhsanuddin, 2024)
This research aims to know and understand the legal protection of land rights holders and to find out the inhibiting factors regarding holders of land rights that have not been certified. The type of research used is normative juridical, which is a type of research that analyses a problem that becomes a legal issue by referring to the application of positive legal norms or legal rules. The result of the research is a form of protection and guarantee of legal certainty by the government with a registration of land rights. In addition, to foster public awareness by conducting socialisation and land counselling through PRONA and PTSL.